Grain Size Variations of Reclaimed CO2 Sand Mold on Hardness and Metal Surface Roughness - Khasanah, Sabtun Ismi; Nurdin, Akhmad; Daryanto, Tri (Universitas Muhammadiyah Yogyakarta, 2023)
Studies on reclaiming CO2 sand mould waste have the opportunity to increase productivity. This research was conducted to learn further about the potential of reclaimed CO2 sand moulds. The effect of the grain size of the reclaimed CO2 sand mould on the hardness and metal surface roughness was analyzed. In addition, a comparison of casting quality analysis was carried out between products using new sand and reclaimed CO2 sand moulds. The CO2 sand moulds were crushed and then sieved using 12, 25 and 40 mesh sieves. The sand waste grains were reclaimed through a detergent washing process. SEM-EDS characterization was carried out to determine the elements contained. The hardness of the casting product was tested using the Rockwell method with a load of 981 N. Meanwhile, the metal surface roughness was characterized through the Roughness Test and visual identification using the JIS 82 standard. Based on the results of the SEM-EDS characterization, the three variations of the reclaimed CO2 sand have the potential to be reused. The quality of the hardness and metal surface roughness of the reclaimed CO2 sand with 25 mesh size variation is close to the quality of the casting product using a new sand mould.